2016
DOI: 10.1038/srep19502
|View full text |Cite
|
Sign up to set email alerts
|

Below-ground interspecific competition for water in a rubber agroforestry system may enhance water utilization in plants

Abstract: Rubber-based (Hevea brasiliensis) agroforestry systems are regarded as the best way to improve the sustainability of rubber monocultures, but few reports have examined water use in such systems. Accordingly, we tested whether interplanting facilitates water utilization of rubber trees using stable isotope (δD, δ18O, and δ13C) methods and by measuring soil water content (SWC), shoot potential, and leaf C and N concentrations in a Hevea-Flemingia agroforestry system in Xishuangbanna, southwestern China. We detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 53 publications
0
17
0
1
Order By: Relevance
“…Deep soil nutrient acquisition is arguably most important in environments where i) the risk of nutrient leaching is high, ii) highly weathered tropical soil orders, such as Ferralsols, are present, or iii) nutrient sources unavailable to crop roots are located in unweathered material. Indeed, while there remain substantial gaps in knowledge on deep root-soil interactions, such as rock weathering and nutrient acquisition below~1 m to 3 m in the soil profile, recent research suggests that these processes are key for improving geochemical cycling in agroforestry systems (Pierret et al 2016), and that these processes are highly related to soil water dynamics in the soil profile (Wu et al 2016). For instance, Bergeron et al (2011) demonstrate an active NO 3 − safety-net role of poplar roots in a TBI system to a depth of 1 m. Studies that descend beyond 3 m are limited, but in other managed tree ecosystems, such as eucalyptus plantations, deep root research shows active tree roots 10 m or deeper (Laclau et al 2001(Laclau et al , 2013.…”
Section: Acquisition Of Deep Soil Nutrientsmentioning
confidence: 99%
“…Deep soil nutrient acquisition is arguably most important in environments where i) the risk of nutrient leaching is high, ii) highly weathered tropical soil orders, such as Ferralsols, are present, or iii) nutrient sources unavailable to crop roots are located in unweathered material. Indeed, while there remain substantial gaps in knowledge on deep root-soil interactions, such as rock weathering and nutrient acquisition below~1 m to 3 m in the soil profile, recent research suggests that these processes are key for improving geochemical cycling in agroforestry systems (Pierret et al 2016), and that these processes are highly related to soil water dynamics in the soil profile (Wu et al 2016). For instance, Bergeron et al (2011) demonstrate an active NO 3 − safety-net role of poplar roots in a TBI system to a depth of 1 m. Studies that descend beyond 3 m are limited, but in other managed tree ecosystems, such as eucalyptus plantations, deep root research shows active tree roots 10 m or deeper (Laclau et al 2001(Laclau et al , 2013.…”
Section: Acquisition Of Deep Soil Nutrientsmentioning
confidence: 99%
“…Wu et al. () stated that competition rather than complementarity likely occurred under cocoa shaded by rubber trees due to the similar root distributions. This implied cocoa plants that have similar rooting system as high canopy shade trees are faced with water competition.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they demonstrate that shade buffers the shaded crop from high temperature and solar radiation, thereby providing a more favorable micro‐climate than in full sun. Finally, it has also been demonstrated that shade trees increase soil organic matter in the long term and consequently improve plant water availability through an enhanced water holding capacity of the soil in some agroforestry systems such as cocoa in Indonesia (Schwendenmann et al., ), coffee in Costa Rica (Cannavo et al., ) and rubber systems in China (Wu, Liu, & Chen, ,b). The perceived long‐term benefits of shade trees sustaining soil fertility and having positive effect on cocoa plant growth and yield on smallholder plots have been shown to be limited (Blaser, Oppong, Yeboah, & Six, ).…”
Section: Introductionmentioning
confidence: 99%
“…To quantify the contribution of potential water sources of plants, a variety of mixing models were developed, such as IsoSource, SIAR, and MixSIR (Moore & Semmens, 2008;Parnell et al, 2013;Phillips & Gregg, 2003;Phillips, Newsome, & Gregg, 2005;Wu, Liu, & Chen, 2016a;Wu, Liu, & Chen, 2016b). In the recent years, a new Bayesian mixing model of MixSIAR was applied to calculate the relative waterabsorbing proportions of potential sources (Ma & Song, 2016;Wu, Liu, & Chen, 2017).…”
Section: Introductionmentioning
confidence: 99%